A Transition Mechanism for the Participation of Renewable Energy Generation Companies in Competitive Electricity Spot Markets - Wang, Kun; Deng, Hui; Yang, Jiajia; Xu, Chengwei; Zhou, Ziqing; Wen, Fushuan; Qi, Donglian (Frontiers in Energy Research, 2022)
Under the China’s 'dual carbon' national goal – reaching peak carbon emissions by 2030 and achieving carbon neutrality by 2060, one of the key issues in China is how to smoothly transit from a fixed-price mode to a competitive market pricing mode for renewable energy generation companies. Aiming at minimizing governmental subsidies and maximizing the fairness among renewable energy generation companies, a multi-agent three-layer transition mechanism with the transactions of green certificates considered is proposed in this paper. Through adjusting subsidy policies, the developed transition mechanism can stimulate the renewable energy generation companies to gradually participate in the competitive electricity spot market. Specifically, a multi-market multi-agent transaction framework in the transition mechanism is first established. Then, in order to derive the important parameters of the transition mechanism, a method that decouples the electricity market and the green certificate market is designed. Finally, the feasibility and efficiency of the proposed transition mechanism are demonstrated through numerical examples.